Prenatal diagnosis of umbilical artery thrombosis in the second trimester: a case report - Esercan, Alev; Ekmekci, Emre (Perinatal Medicine Foundation, 2021)
Objective Thrombosis of umbilical artery is a rare condition. The diagnosis is established commonly in the third trimester after detection of fetal distress or intrauterine growth retardation, or could be established after delivery. Also, the management of the condition is conflicting after the diagnosis. Case(s) Here we reported an umbilical artery thrombosis case that was diagnosed in the second trimester after referral for an umbilical cord cyst. After the diagnosis at 24th week of pregnancy, she had been followed up weekly. She had been delivered electively at the 34th week of pregnancy uneventfully. The diagnosis was confirmed postnatally. Conclusion The prenatal diagnosis of umbilical arterial thrombosis is so important to prevent perinatal morbidity. When umbilical cord cysts are detected, further evaluation is required in terms of umbilical artery thrombosis.